P056: Rural versus urban pre-hospital and in-hospital mortality following a traumatic event in Québec, Canada. (15th May 2017) - Fleet, R.; Tounkara, F.; Turcotte, S.; Ouimet, M.; Dupuis, G.; Poitras, J.; Tanguay, A.B.; Fortin, J.; Trottier, J.; Ouellet, J.; Lortie, G.; Plant, J.; et al.
Abstract : Introduction: Trauma remains the primary cause of death in people under 40 in Québec. Although trauma care has dramatically improved in the last decade, no empirical data on the effectiveness of trauma care in rural Québec are available. This study aims to establish a portrait of trauma and trauma-related mortality in rural versus urban pre-hospital and hospital settings.Methods: Data for all trauma victims treated in the 26 rural hospitals and 32 Level-1 and Level-2 urban trauma centres was obtained from Québec's trauma registry (2009-2013). Rural hospitals were located in rural small towns (Statistics Canada definition), provided 24/7 physician coverage and admission capabilities. Study population was trauma patients who accessed eligible hospitals. Transferred patients were excluded. Descriptive statistics were used to compare rural with urban trauma case frequency, severity and mortality and descriptive data collected on emergency department (ED) characteristics. Using logistic regression analysis we compared rural to urban in-hospital mortality (pre-admission and during ED stay), adjusting for age, sex, severity (ISS), injury type and mode of transport.Results: Rural hospitals (N=26) received on average 490 000 ED visits per year and urban trauma centres (N=32), 1 550 000. Most rural hospitals had 24/7 coverage and diagnostic equipment e.g. CT scanners (74 %), intensive care units (78 %) and general surgical services (78 %), but little access to other consultants. About 40% of rural hospitals were more than 300 km from a Level-1 or Level-2 trauma centre. Of the 72 699 trauma cases, 4703 (6.5%) were treated in rural and 67 996 (93.5%) in urban hospitals. Rural versus urban case severity was similar: ISS rural: 8.6 (7.1), ISS urban: 7.2 (7.2). Trauma mortality was higher in rural than urban pre-hospital settings: 7.5% vs 2.6%. Reliable pre-hospital times were available for only a third of eligible cases. Rural mortality was significantly higher than urban mortality during ED stays (OR (95% IC): 2.14 (1.61-2.85)) but not after admission (OR (95% IC): 0.87 (0.74-1.02)).Conclusion: Rural hospitals treat equally severe trauma cases as do urban trauma centres but with fewer resources. The higher pre-hospital and in-ED mortality is of grave concern. Longer rural transport times may be a factor. Lack of reliable pre-hospital times precluded further analysis.